Factors Affecting Pouch Milk Purchase in Kathmandu - Shrestha, Sajeeb Kumar (Tribhuvan University Journal, 2019)
This research attempts to measure factors affecting pouch milk purchase in Nepalese context. Positivist approach was used and descriptive and causal study was designed. Questionnaire survey was done and structured questionnaires were designed to collect data. Subjects of the study were respondents who purchase pouch milk regularly for household consumption. 200 samples were taken based on convenience sampling method. Data were analyzed thoroughly by reliability analysis, descriptive statistics, correlation analysis and regression analysis. The research confirmed quality and brand name had influence on pouch milk purchase decision. No support was found for price, availability and promotion in pouch milk purchase context.